Learning Media Game Me Educational Android on Mathematics Class II Elementary School - Jihan Nazira Tazkiya Vega; Novanita Whindi Arini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills. Research and development methods or in English Research and Development are research methods used to produce certain products, and test the effectiveness of these products. Create and develop as well as determine the feasibility of educational game media as learning media that are suitable for use by educators and students. After being tested, it will receive a response to criticism and suggestions for evaluating the AAP educational game media product. The conclusion of this research, the AAP educational game is a learning media to support and assist the learning process